Clinical correlates of hearing voices among people seeking interventions for dissociation: a cross-cultural investigation. Issue 4 (1st October 2020) - Fung, Hong Wang; Chan, Chitat; Ross, Colin A.
ABSTRACT: Auditory hallucinations are common among people seeking treatment for trauma and dissociation and can result in diagnostic challenges. This study examined the correlates of hearing voices in two samples of people seeking interventions for dissociation – a sample of 83 English speakers and a sample of 82 Chinese speakers. We found that, compared with depersonalization, hearing voices was more closely associated with trauma and other dissociative phenomena (especially identity dissociation) across two samples from different cultures. We recommend that careful assessment of trauma and dissociation should take place before a clinician assumes that auditory hallucinations are a psychotic symptom. Our findings support the idea that at least some forms of hearing voices are a cross-culturally occurring trauma-related dissociative phenomenon.